Altered sleep structure in patients with end-stage renal disease - Elias, Rosilene M.; Chan, Christopher T.; Bradley, T. Douglas (Sleep medicine, 2016)
•Patients with end-stage renal disease (ESRD) have a higher prevalence of sleep disorders than individuals without ESRD.•ESRD associated with reduced total and REM sleep times after controlling for the severity of sleep apnea, age, and body mass index.•The cause of reduced sleep times could be related to uremia or fluid overload or both. Although symptoms of sleep disturbances are widely recognized in end-stage renal disease (ESRD), the effect of uremia on sleep structure has not been well investigated. We hypothesized that compared to individuals without ESRD, those with ESRD would have altered sleep structure after controlling for the severity of sleep apnea (SA). We studied 57 ESRD patients (42 men) and 57 controls (46 men) who had undergone polysomnography. Control subjects were matched to the ESRD patients by age, body mass index (BMI), frequency of periodic leg movements per hour of sleep, and the frequency of apneas and hypopneas per hour of sleep [apnea–hypopnea index (AHI)]. The AHI and the percentage of patients with an AHI ≥15 were similar between ESRD and control groups. However, total (p = 0.002), rapid eye movement (REM) (p = 0.007), and non-REM (p = 0.022) sleep times were lower in ESRD patients than in the control group. In a multivariable analysis adjusted for age, sex, AHI, BMI, arousal index, and diabetes, ESRD remained independently associated with lower REM (p = 0.021) and total sleep times (p = 0.026). ESRD is independently associated with reduced total and REM sleep times after controlling for the severity of SA and other variables. Although we could not identify the cause of reduced sleep times, these could be related to uremia or fluid overload or both. Accordingly, our data provide a strong rationale for examining the effects of intensifying dialysis on sleep structure in ESRD patients.